Female Labor Supply and Parental Leave Benefits: The Causal Effect of Paying Higher Transfers for a Shorter Period of Time - Annette Bergemann; Regina T. Riphahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We study the labor supply effects of a change in child-subsidy policy designed to both increase fertility and shorten birth-related employment interruptions. The reform yields most of the intended effects.
Keywords: J13; J21; 330; female labor supply; fertility; child subsidy; parents money